Pengembangan E-Modul Berbantuan Heyzine Flipbook pada Materi Aku dan Kebutuhanku - Dwi Oktaviani; Rais Hidayat; Irvan Permana (Mataram University, 2026)
Science and social studies (IPAS) instruction in Grade IV-A of SDN Cimpaeun 3, Depok City, still relies mainly on printed textbooks, while the use of digital technology remains limited, resulting in suboptimal student engagement and learning outcomes. This study aims to develop, validate, and test the effectiveness of a Heyzine Flipbook-assisted e-module on the topic of